Toll-like Receptor-4: A New Target for Preterm Labour Pharmacotherapies? - Robertson, Sarah A.; Wahid, Hanan Hamimi; Peck, Yin Chin; Hutchinson, Mark R.; Lachlan, M. Moldenhauer; A. Keelan, Jeffrey (2018)
Inflammatory activation, a major driver of preterm birth and subsequent neonatal morbidity, is an attractive pharmacological target for new preterm birth therapeutics. Inflammation elicited by intraamniotic infection is causally associated with preterm birth, particularly in infants delivered ≤34 weeks' gestation. However, sterile triggers of PTB, including placental ischaemic injury, uterine distention, cervical disease, or imbalance in the immune response, also act through inflammatory mediators released in response to tissue damage. Toll-like Receptors (TLRs) are critical upstream gate-keepers controlling the inflammatory activation that precedes preterm delivery, as well as in normal term labour. In particular, TLR4 is implicated for its capacity to sense and integrate a range of disparate infectious and sterile pro-inflammatory triggers, and so acts as a point-ofconvergence through which a range of infectious and sterile agents can activate and accelerate the parturition cascade. Recent studies point to the TLR4 signalling complex as a tractable target for the inhibition of fetal, placental & intraamniotic inflammatory cytokine production. Moreover, studies on mice show that novel small molecule antagonists of TLR4 signalling are highly effective in preventing preterm birth induced by bacterial mimetic LPS, heat-killed E. coli or the TLR4-dependent pro-inflammatory lipid, Platelet Activating Factor (PAF). In this review, we discuss the role of TLR4 in regulating the timing of birth and the potential utility of TLR4 antagonists as novel therapeutics for preterm delivery.